2012
DOI: 10.1016/j.physletb.2011.11.064
|View full text |Cite
|
Sign up to set email alerts
|

Deconfinement and chiral restoration in non-local PNJL models at zero and imaginary chemical potential

Abstract: We study the deconfinement and chiral restoration transitions in the context of non-local PNJL models, considering the impact of the presence of dynamical quarks on the scale parameter appearing in the Polyakov potential. We show that the corresponding critical temperatures are naturally entangled for both zero and imaginary chemical potential, in good agreement with lattice QCD results. We also analyze the Roberge Weiss transition, which is found to be first order at the associated endpoint.PACS numbers: 12.3… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 63 publications
1
35
0
Order By: Relevance
“…[45,46]). Something similar happens in the region of imaginary chemical potential, where the entanglement between both transitions occurs in a natural way within nonlocal models [24], while in the PNJL model it can be obtained only after e.g. the inclusion of an eight-quark interaction [47].…”
Section: Numerical Resultsmentioning
confidence: 99%
“…[45,46]). Something similar happens in the region of imaginary chemical potential, where the entanglement between both transitions occurs in a natural way within nonlocal models [24], while in the PNJL model it can be obtained only after e.g. the inclusion of an eight-quark interaction [47].…”
Section: Numerical Resultsmentioning
confidence: 99%
“…Results have first been obtained within a staggered fermion formulation of QCD, but efforts have been undertaken to confirm their universality also within a Wilson fermion approach [35,[37][38][39] leading to the same qualitative phase diagram [35]. The Roberge-Weiss endpoint transition, or variants of it, also has been studied in many other different contexts and QCD-like theories [40][41][42][43][44][45][46][47][48][49][50][51].…”
Section: Phase Diagram For Imaginary Chemical Potentialmentioning
confidence: 99%
“…ii) Early studies have shown that the RW endpoint transition is first order for small quark masses, second order for intermediate masses, and again first order for large masses; the three regions are separated by two tricritical points [13][14][15]. The emergence of this interesting structure has induced many further studies in effective models [28][29][30][31][32][33][34][35][36][37][38][39][40] which try to reproduce the essential features of QCD. Moreover, interesting proposals have been made on the connection of this phase structure with that present at µ B = 0 (the so-called Columbia plot) and on the possibility to exploit the whole phase structure at imaginary chemical potential in order to clarify currently open issues on the phase structure at µ B = 0, like the order of the chiral transition for N f = 2 [21,24].…”
Section: Introductionmentioning
confidence: 99%